Infection by AIDS virus and HTLV-I at the Hospital Universitario del Valle, Cali, Colombia (Colombia Medica, 1988)
Patients receiving frequent transfusions of blood products are exposed to viral infections, mainly with the human immunodeficiency virus (HIV). We have screened 57 of these patients, 55 of them hemophiliacs, for HIV and retrovirus I (HTVL-I). We found 3 (5.3%) antibodies for HIV and 2 (3.5%) for HTLV-I. We here present a discussion of this low seropositivity rate for HIV in these particular patients. Compared with other countries, there was a very interesting finding of two samples positive for HTLV-I.